The Effectiveness of the SIAPP Digital Learning Platform in Improving Community Self-Efficacy in Providing Basic Life Support in Pontianak City, Indonesia - Uti Rusdian Hidayat; Fauzan Alfikrie; Debby Hatmalyakin; Ali Akbar; Defa Arisandi; Nurpratiwi Nurpratiwi; Mimi Amaludin; Ruhil Iswara; Nurannisa Nurannisa; Ihsan Angga Anjarwadi; Delvi Yanto (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Out-of-hospital cardiac arrest (OHCA) remains a major public health challenge globally, with low survival rates largely attributed to delayed or inadequate Basic Life Support (BLS) provided by lay responders. Limited access to educational resources and low self-efficacy among community members further hinder effective early intervention. This study aimed to evaluate the effectiveness of the First Aid Learning Administration Information System (SIAPP) in improving community self-efficacy in providing BLS in Pontianak City, Indonesia. A quasi-experimental study using a one-group pretest–posttest design was conducted among 33 community participants recruited through convenience sampling. The study, including the intervention and outcome assessments, was conducted over 2 weeks. The intervention consisted of SIAPP-based first-aid training. Self-efficacy was measured using a structured questionnaire before and after the intervention. Data were analyzed using the Wilcoxon signed-rank test to determine differences in self-efficacy scores. Participants’ self-efficacy improved significantly after the intervention (p = 0.001). The findings indicate that SIAPP effectively increases community members' confidence in performing BLS procedures. SIAPP is an effective and scalable digital learning platform for improving community self-efficacy in BLS provision. Its implementation may strengthen early response capacity in OHCA cases and improve community-based emergency preparedness Keywords: SIAPP, Self-efficacy, Basic Life Support, Out-of-Hospital Cardiac Arrest, Health Education